A Critical Review of Dr. Heri Gunawan’s Thoughts on the Concept and Implementation of Character Education - Ahmad Fadha Ilul Firdaus; Matroni Matroni; Yetti Hidayatullah (Electronic Journal of Education, Social Economics and Technology, 2025)
Character education is a fundamental part of the Indonesian education system, aimed at shaping a generation with noble character and strong personality. In his book Pendidikan Karakter: Konsep dan Implementasi (Character Education: Concept and Implementation), Dr. Heri Gunawan offers a concept of character education based on a balance between cognitive, affective, and psychomotor aspects. This study aims to conduct a critical review of Dr. Heri Gunawan’s thoughts by examining the concept, implementation, and its relevance within the context of education in Indonesia. The research method used is a literature review with a qualitative descriptive approach. The findings show that Dr. Heri Gunawan’s concept of character education emphasizes the internalization of moral values through a systematic and integrative learning process. However, challenges in its implementation are still evident, particularly in the areas of curriculum design, teacher preparedness, and evaluation of its effectiveness. This study recommends the need for synergy between education policy, teacher readiness, and more adaptive implementation strategies to ensure that character education can be effectively realized.